The transformation of political communication in China from propaganda to hegemony - Zhang, Xiaoling, Dr. (Series on contemporary China, 2011)
"This book examines different dynamics such as marketisation, globalisation and new media technologies that have driven the transformation of China's media industry--one of the primary battlegrounds where ideological, social and economic struggles are fought--against the backdrop of the growing tensions between economic growth, globalisation, and political control in China."--